Opinions on exercise and rehabilitation of patients with CKD: survey results among practicing nephrologists - K. A. Vishnevskii; R. P. Gerasimchuk; A. Yu. Zemchenkov; U. A. Tikhovskaya; V. Yu. Ryasnyansky (Nephrology and Dialysis, 2025)
Introduction . Increased physical activity in patients with chronic kidney disease (CKD) is associated with numerous proven benefits. However, physical rehabilitation programs are rarelu integrated into standard clinical practice, and the reasons for this remain unclear. The study aimed to explore nephrologist’s opinions regarding exercise and physical activity in patients with CKD. Methods . An anonymous survey was conducted among nephrologists working in outpatient dialysis units in the between May and July 2025. Results. A total of 98 physicians from dialysis centers participated in the survey. The average age of respondents was 42(10) years, and their work experience was 14(9) years. Respondents themselves engaged in physical activity infrequently (median 1 time per week (